Hosoya Polynomials of The Width Distance of Some Cog-Special Graphs - Tahir Ismail; Ahmed Ali (Al-Rafidain Journal of Computer Sciences and Mathematics)
In  this paper, we give some definitions and  properties of the width distance and find the Hosoya polynomials, Wiener indices, and the average distances of some special cog-graphs with respect  to the width distance.